2020
DOI: 10.3389/fpsyt.2020.00546
|View full text |Cite
|
Sign up to set email alerts
|

The THINC-it Tool for Cognitive Assessment and Measurement in Major Depressive Disorder: Sensitivity to Change

Abstract: Background Herein, we sought to determine the sensitivity to change in cognitive function, as measured by the THINC-it tool, in a sample of adults with major depressive disorder (MDD) receiving standardized antidepressant therapy. Methods Adults meeting the DSM-5 criteria for MDD with at least moderate depressive symptom severity [ i.e. , Montgomery Åsberg Depression Rating Scale (MADRS) total score ≥ 20] were treated with open-label vortioxet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…In the study herein, through the THINC-it test, the cognitive function including subjective cognition, objective cognition and comprehensive score of MDD were significantly different from healthy controls. In accordance with previous research, the cognitive function of patients with MDD was significantly impaired when compared to healthy individuals ( 10 , 13 , 23 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study herein, through the THINC-it test, the cognitive function including subjective cognition, objective cognition and comprehensive score of MDD were significantly different from healthy controls. In accordance with previous research, the cognitive function of patients with MDD was significantly impaired when compared to healthy individuals ( 10 , 13 , 23 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…The THINC-it tool is a simple cognitive screening tool, divided into subjective cognition and objective cognition assessment, including attention, information processing speed, executive function, memory and learning function, which can comprehensively measure cognitive impairment in MDD. The THINC-it has been validated at home and abroad ( 10 , 11 , 23 ). Our team has previously validated and reported on psychometric characteristics of the Chinese version of the THINC-it tool, and it is also the first-ever clinical cognitive screening tool applied to Chinese patients with MDD ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Published June 11, 2020 , Stang, 2010 , Shuwa et al, 2021 , Sonnweber et al, 2021 , Taboada et al, 2021 , Todt et al, 2021 , Wong et al, 2020 , Zhou et al, 2021 , Ghosn et al, 2021 , Say et al, 2021 , Pilotto et al, 2021 , Liyanage-Don et al, 2021 , Miyazato et al, 20202020 , González et al, 2021 , Fernández-de-las-Peñas et al, 2021 , Fernández-de-Las-Peñas et al, 2021 , Arnold et al, 2021 , Fortini et al, 2021 , García-Abellán et al, 2021 , Ong et al, 20212021 , PHOSP-COVID Collaborative Group et al, 2021 , Skala et al, 2021 , Sykes et al, 2021 , Santis et al, 2020 , van den Borst et al, 2020 , Venturelli et al, 2021 , IL6 - Clinical: Interleukin 6, Plasma. Accessed June 26, 2021 , Elkan et al, 2021 , Frontera et al, 2021 , Garrigues et al, 2020 , Havervall et al, 2021 , Rogers et al, 2020 , Hoffman and Vilensky, 2017 , Komaroff and Lipkin, 2021 , Higgins et al, 2021 , Douaud et al, 2021 , Lee et al, 2021 , Guedj et al, 2021 , Libby and Lüscher, 2020 , Oronsky et al, 2021 , Yong, 2021 , Sartori et al, 2012 , Rosenblat et al, 2014 , Sonneville et al, 2009 , Gałecki et al, 2018 , Heckenberg et al, 2018 , Xiong et al, 2020 , Taquet et al, 2021 , McIntyre et al, 2019 , Miskowiak et al, 2017 , McIntyre et al, 2020 , McIntyre et al, 2017 , McIntyre et al, 2013 , Ustün and Kennedy, 2009 , Abdallah et al, 2021 , Buonsenso et al...…”
Section: Uncited Referencesmentioning
confidence: 99%
“…The THINC-it Tool has been previously validated as a screening tool and as a repeat measure for cognitive function in adults with MDD [ 12 , 23 ]. A variant of the DSST was included in the THINC-it Tool and accounted for significant variance in the tool’s overall performance, suggesting that the DSST alone may provide sufficient conceptual coverage [ 12 , 23 , 24 ]. This study demonstrated the validity of the app-based Cognition Kit DSST to assess cognitive impairment in patients with MDD and represents a personalized assessment approach that may help guide MBC to inform psychotherapeutic and pharmacologic treatment options.…”
Section: Discussionmentioning
confidence: 99%